Indonesian children fecal microbiome from birth until weaning was different from microbiomes of their mothers - Wei Wei Thwe Khine; Endang Sutriswati Rahayu; Ting Yi See; Sherwin Kuah; Seppo Salminen; Jiro Nakayama; Yuan-Kun Lee (TAYLOR & FRANCIS INC, 2022)
Gastrointestinal (GI) microbiota play an important role in human health and wellbeing and the first wave of gut microbes arrives mostly through vertical transmission from mother to child. This study has undertaken to understand the microbiota profile of healthy Southeast Asian mother-infant pairs. Here, we examined the fecal, vaginal and breast milk microbiota of Indonesian mothers and the fecal microbiota of their children from less than 1 month to 48 months old. To determine the immune status of children and the effect of diet at different ages, we examined the level of cytokines, bile acids in the fecal water and weaning food frequency. The fecal microbiota of the children before weaning contained mainlyBacteroidesandBifidobacterium, which presented at low abundance in the samples of mothers. After weaning, the fecal microbiome of children was mainly of thePrevotellatype, with decreasing levels ofBifidobacterium, thus becoming more like the fecal microbiome of the mother. The abundance of infant fecal commensals generally correlated inversely with potential pathogens before weaning. The fecalBifidobacteriumin children correlated inversely with the consumption of complex carbohydrates and fruits after weaning. The specific cytokines related to the proliferation and maturation of immunity were found to increase after weaning. A decreasing level of primary bile acids and an increase of secondary bile acids were observed after weaning. This study highlights the change in the GI microbiota of infants to adult-type microbiota after weaning and identifies diet as a major contributing factor.